The Euro-Atlantic Security System in the 21st Century From Cooperation to Crisis - Zięba, Ryszard (Global Power Shift,, 2018)
This book examines the evolution of the Euro-Atlantic security system, from cooperation to rivalry and crisis, since the beginning of the 21st century. By highlighting the causes, manifestations and international consequences of this evolution, the author describes a stage of crisis in the security system, characterized by increasing rivalry for spheres of influence, militarization of policies and the suspension of cooperation due to the growing divergence between the interests of the West - now including the Central European states - and Russia, leading to a subsequent reconfiguration of the world order. Adopting a neo-realistic approach, the author demonstrates that members of the Euro-Atlantic security system, irrespective of the values they claim to hold, are guided in their actions on the international stage by clearly defined interests. The first part of the book analyses the nature of the Euro-Atlantic security system, while the second part illustrates the limited success of Euro-Atlantic collaboration, for example in combating terrorism. Lastly, the third part discusses the consequences of the crisis, such as the conflict in Ukraine, and prospects for the future evolution of the Euro-Atlantic security system. .